2014
DOI: 10.1167/14.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Davida Teller Award Lecture 2013: The importance of prediction and anticipation in the control of smooth pursuit eye movements

Abstract: The ability of smooth pursuit eye movements to anticipate the future motion of targets has been known since the pioneering work of Dodge, Travis, and Fox (1930) and Westheimer (1954). This article reviews aspects of anticipatory smooth eye movements, focusing on the roles of the different internal or external cues that initiate anticipatory pursuit.We present new results showing that the anticipatory smooth eye movements evoked by different cues differ substantially, even when the cues are equivalent in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 74 publications
2
53
0
Order By: Relevance
“…Anticipatory smooth pursuit is often observed when the object's motion is expected. In this case, the latency of pursuit onset can be shortened and the eyes can even start moving before the target (Kowler et al 2014). Anticipatory smooth pursuit can be induced by the repeated presentation of the same motion trajectory (Kowler and Steinman 1979), by a prior cue indicating the target motion direction (de Hemptinne et al 2008), by the history of recent trials (Collins and Barnes 2009), or when the target motion is generated by the observers themselves (Steinbach 1969).…”
Section: Humans Often Have To Track Motion That Is Generated By Themsmentioning
confidence: 99%
“…Anticipatory smooth pursuit is often observed when the object's motion is expected. In this case, the latency of pursuit onset can be shortened and the eyes can even start moving before the target (Kowler et al 2014). Anticipatory smooth pursuit can be induced by the repeated presentation of the same motion trajectory (Kowler and Steinman 1979), by a prior cue indicating the target motion direction (de Hemptinne et al 2008), by the history of recent trials (Collins and Barnes 2009), or when the target motion is generated by the observers themselves (Steinbach 1969).…”
Section: Humans Often Have To Track Motion That Is Generated By Themsmentioning
confidence: 99%
“…By integrating visual inputs with past experience and cues, the oculomotor system can overcome sensory delays and noise to produce eye movements matching current target movement. In the pursuit system, this allows, for example, anticipatory smooth eye movements (Dodge, Travis, & Fox, 1930;Hayhoe, McKinney, Chajka, & Pelz, 2012;Kowler, Aitkin, Ross, Santos, & Zhao, 2014;Westheimer, 1954) or zero-lag smooth pursuit tracking of a sinusoidal target motion (Dodge et al, 1930;Orban de Xivry et al, 2013). In the saccadic system, predictive saccades can be observed when tracking a target jumping at a fixed frequency (Shelhamer & Joiner, 2003), or a bouncing ball (Diaz, Cooper, Rothkopf, & Hayhoe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Control of smooth pursuit eye movements is based on a dynamic interplay between low-level retinal and high-level extraretinal signals (Barnes, 2008; Lisberger, 2010; Kowler et al, 2014). Sensory and cognitive contributions are closely interwoven, but rely on differential neuronal resources.…”
Section: Discussionmentioning
confidence: 99%
“…Some findings point to functional associations with antisaccade performance (Ettinger et al, 2008; Haraldsson et al, 2010; Kasparbauer et al, 2015), but differences foremost showed up in BOLD responses. Smooth pursuit seems ideal for studying different mechanisms involved in oculomotor control, because it relies on a sophisticated interplay between motion perception, sensorimotor transformation, and anticipatory abilities (Lisberger, 2010; Kowler et al, 2014). However, the link between both polymorphisms and individual variations in pursuit has not been investigated appropriately yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation